Are the anti-arrhythmic effects of omega-3 fatty acids due to modulation of myocardial calcium handling? - Sankaranarayanan, Rajiv; Venetucci, Luigi (Frontiers in Physiology, 2012)
Both animal and clinical studies have demonstrated that omega -3 fatty acids have anti-arrhythmic properties. It has been suggested that these anti-arrhythmic effects are due to modulation of the activity of various myocardial calcium handling proteins such as ryanodine receptor, L type calcium current and sodium /calcium exchanger. In this article, we review all the data available on the effects of omega-3 fatty acids on ventricular myocardial calcium handling. In addition we highlight some unanswered questions and discuss possible therapeutic benefits of omega-3 fatty acids.